2019
DOI: 10.21470/1678-9741-2018-0322
|View full text |Cite
|
Sign up to set email alerts
|

The Status and Research Progress on Vitamin D Deficiency and Atrial Fibrillation

Abstract: Atrial fibrillation is a common type of arrhythmia and is an important cause of stroke and heart failure. vitamin D is an emerging risk factor of AF, and is implicated in the pathophysiology of atrial fibrillation. It has been established that this vitamin is extensively involved in the regulation of both the renin angiotensin aldosterone system and the immune system. Epidemiological studies have not yet reached a consensus on the possible association between vitamin D deficiency and atrial fibrillation. Bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Some studies suggest a direct correlation between atrial fibrillation and vitamin D deficiency [ 95 , 96 , 97 ]. However, other studies did not find a connection between vitamin D levels and the incidence of atrial fibrillation [ 98 , 99 , 100 ]. It would be important to better understand the link between vitamin D and calcium, because it is known that calcium overload causes myocytes apoptosis and cardiac failure [ 101 , 102 ].…”
Section: Vitamin Dmentioning
confidence: 97%
“…Some studies suggest a direct correlation between atrial fibrillation and vitamin D deficiency [ 95 , 96 , 97 ]. However, other studies did not find a connection between vitamin D levels and the incidence of atrial fibrillation [ 98 , 99 , 100 ]. It would be important to better understand the link between vitamin D and calcium, because it is known that calcium overload causes myocytes apoptosis and cardiac failure [ 101 , 102 ].…”
Section: Vitamin Dmentioning
confidence: 97%
“…On top of that, scientists have found that vitamin D deficiency may increase the risk of atrial fibrillation (AF), possibly since vitamin D can reduce inflammation by inducing interleukin 10 (IL-10) production and reducing the production of interferon-γ, and tumor necrosis factor-alpha (TNF-α), IL-6, and IL-12 [ 51 ], and vitamin D inhabitant the renin-angiotensin system (RAS) [ 52 ]. A review study in 2019 on the effect of vitamin D on atrial fibrillation reported that further basic and precise studies are required in this area [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, vitamin D was associated with an inflammatory milieu and could increase the synthesis of C-reactive protein (CRP) directly or indirectly, which was crucial for the pathogenesis of AF ( 43 ). However, studies have suggested that vitamin D deficiency may be a consequence, not a cause of inflammation ( 44 ). In a word, the potential mechanisms of vitamin D and AF are still not fully illuminated and in dispute.…”
Section: Discussionmentioning
confidence: 99%